How Are They Doing? University Outcomes of International Students Studying in Canada - Grayson, J. (Comparative and International Education / Éducation comparée et internationale, 2023)
Globally, over the past few decades, there has been a considerable increase in research on the host country experiences of international students. This is not the case for examinations of university outcomes. As a result, in this article, as a first step, comparisons are made between the academic achievement (GPA), satisfaction, and intent of international students to return to their university as compared to Canadian domestic students at three points in time. First, I show that over several decades there has been little difference in the outcomes of international and domestic students. Second, based on cluster analysis and analyses of covariance, outcomes of contemporary students, as embodied in an “‘adjustment index,”’ are compared and dissected. This procedure shows that while international students suffer from an overall disadvantage in adjustment, there is considerable within group difference. Overall, while there is much room for improvement, the outcomes of international students are hopeful.